2020
DOI: 10.1371/journal.pone.0229287
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes from neonates and adults have a similar capacity to adapt their cytokine production after previous exposure to BCG and β-glucan

Abstract: The Bacillus Calmette-Gué rin (BCG) vaccine is administered at birth in tuberculosis (TB) endemic countries. BCG vaccination is also associated with protective non-specific effects against non-tuberculous infections. This seems at least in part mediated through induction of innate immune memory in myeloid cells, a process termed trained immunity. β-glucan, a component of the fungal cell wall from Candida albicans, induces a trained immunity phenotype in human monocytes with hyper-responsiveness against unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Meanwhile, it is different than adaptive because it shows nonspecific response compared to T/B cell responses [26]. The overall values of trained immunity is attributed to long-term sensitivity of innate immune cells to any microbial stimuli, increasing the response to the same and different subsequent stimuli, and consequently increased cytokine production (not only against TB but also against bacteria, viruses, and even parasites) mediated by monocytes and natural-killer (NK) cells with a memory-like effect via and chromatin remodelling through histone modifications, leading to an enhanced gene transcription upon re-stimulation (especially the up-regulation of IL-1ß) [27], and changes in intracellular metabolism [28][29][30][31]. When trained immunity is induced in monocytes in response to microbial molecules as ß-glucan, there is a relevant increase in cellular aerobic glycolysis and glutamine metabolism via a central regulatory mechanism of mTOR-HIF1a pathway [32,33].…”
Section: Vaccine Age and Gender Relation To Covid-19 Infectionmentioning
confidence: 99%
“…Meanwhile, it is different than adaptive because it shows nonspecific response compared to T/B cell responses [26]. The overall values of trained immunity is attributed to long-term sensitivity of innate immune cells to any microbial stimuli, increasing the response to the same and different subsequent stimuli, and consequently increased cytokine production (not only against TB but also against bacteria, viruses, and even parasites) mediated by monocytes and natural-killer (NK) cells with a memory-like effect via and chromatin remodelling through histone modifications, leading to an enhanced gene transcription upon re-stimulation (especially the up-regulation of IL-1ß) [27], and changes in intracellular metabolism [28][29][30][31]. When trained immunity is induced in monocytes in response to microbial molecules as ß-glucan, there is a relevant increase in cellular aerobic glycolysis and glutamine metabolism via a central regulatory mechanism of mTOR-HIF1a pathway [32,33].…”
Section: Vaccine Age and Gender Relation To Covid-19 Infectionmentioning
confidence: 99%
“…We have also shown that plasma BDG levels are associated with reduced expression of Dectin-1 and NKp30 on monocytes and NK cells respectively, indicating direct cellular activation and inflammation by BDG. Circulating BDG contributes to low grade inflammation [28,37] and may enhance trained immunity at the epigenetic level [38,39]. Therefore, assessment of BDG levels may be useful in predicting the risk of PLWH to develop non-AIDS comorbidities [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies displayed a pathogen dose-dependent induction of either innate memory by priming with low doses, or tolerance by high doses of sequential challenges with LPS, especially in macrophages and microglia ( 86 88 ). Moreover, cellular maturation is another important factor, influencing adaptive features through distinct signaling mechanisms ( 89 , 90 ). Activation of the phosphoinositide 3-kinase (PI3K)/mechanistic target of rapamycin (mTOR) pathway is critical for the induction of trained immunity in macrophages leading to an increased inflammatory response ( 91 ).…”
Section: Long-term Adaptation Of Neutrophilsmentioning
confidence: 99%